ANALISIS PROFITABILITAS USAHA WARUNG MAKAN PECEL LELE DI BATURAJA TIMUR - Purwadi, Veri Kurniawan, Putri Ayu Ogari, (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2024)
This study aims to analyze the profitability of the pecel lele business. The study was conducted in Baturaja Timur District, OKU Regency, where the research location was chosen intentionally, because it was considered to be in accordance with the criteria needed in the study. The study was conducted using a survey method. While the sampling used the census method, which was 33 catfish pecel entrepreneurs. The purpose of the study was analyzed using the profitability formula, where previously the costs, revenues and income were also calculated each month from the pecel lele business. The results of the study showed that the pecel lele business was profitable because it had a profitability value of 104.98%.